Tools for faculty assessment of interdisciplinary competencies of healthcare students: an integrative review - Brownie, Sharon; Blanchard, Denise; Amankwaa, Isaac; Broman, Patrick; Haggie, Marrin; Logan, Carlee; Pearce, Amy; Sampath, Kesava; Yan, Ann-Rong; Andersen, Patrea (Frontiers in Medicine, 2023)
Increasingly, interprofessional teamwork is required for the effective delivery of public health services in primary healthcare settings. Interprofessional competencies should therefore be incorporated within all health and social service education programs. Educational innovation in the development of student-led clinics (SLC) provides a unique opportunity to assess and develop such competencies. However, a suitable assessment tool is needed to appropriately assess student progression and the successful acquisition of competencies. This study adopts an integrative review methodology to locate and review existing tools utilized by teaching faculty in the assessment of interprofessional competencies in pre-licensure healthcare students. A limited number of suitable assessment tools have been reported in the literature, as highlighted by the small number of studies included. Findings identify use of existing scales such as the Interprofessional Socialization and Valuing Scale (ISVS) and the McMaster Ottawa Scale with Team Observed Structured Clinical Encounter (TOSCE) tools plus a range of other approaches, including qualitative interviews and escape rooms. Further research and consensus are needed for the development of teaching and assessment tools appropriate for healthcare students. This is particularly important in the context of interprofessional, community-partnered public health and primary healthcare SLC learning but will be of relevance to health students in a broad range of clinical learning contexts.